1968
DOI: 10.1128/jb.95.2.546-558.1968
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Deoxyribonucleic Acid in Haemophilus influenzae I. X-Ray Sensitivity of Ultraviolet-sensitive Mutants and Their Behavior as Hosts to Ultraviolet-irradiated Bacteriophage and Transforming Deoxyribonucleic Acid

Abstract: Seven mutants of Haemophilus influenzae were isolated by the criterion of sensitivity to ultraviolet (UV) inactivation of colony formation. These mutants and the wild type were characterized with regard to X-ray inactivation of colony formation, UV induction of division inhibition, the ability of the eight strains to act as recipients to UV-irradiated H. influenzae phage and transforming deoxyribonucleic acid (DNA), and the influence of acriflavine on the survival of UV-irradiated transforming DNA with these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0

Year Published

1972
1972
1997
1997

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(87 citation statements)
references
References 16 publications
1
86
0
Order By: Relevance
“…By contrast, the transduction frequencies of the terials and Methods cml-r and tet-r markers in MS3878 were approximately the same between the UV-sensitive mutants and the original strains (Table 2). From these results, it was concluded that the UV-sensitive mutants were the recombinationdeficient type mutants as reported for the recmutants (5,11,22,25).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…By contrast, the transduction frequencies of the terials and Methods cml-r and tet-r markers in MS3878 were approximately the same between the UV-sensitive mutants and the original strains (Table 2). From these results, it was concluded that the UV-sensitive mutants were the recombinationdeficient type mutants as reported for the recmutants (5,11,22,25).…”
supporting
confidence: 62%
“…UV-sensitive mutants were obtained by a slight modification of the method described by Setlow et al (22). An overnight culture of S. aureus MS3937-1 was diluted 100-fold with fresh broth and incubated with shaking at 37 C. After incubation for 3 hr, 5 ml of this culture was suspended in 5 ml of broth containing 200 gg of NG/ml.…”
mentioning
confidence: 99%
“…The bacterial strains, bacteriophage and plasmids used in this study are listed in Table 1 (Setlow et al, 1968;Tabor and Richardson, 1985;Kunkel et al, 1987;Tomb et al, 1989;. H. influenzae strains were grown as described previously (Anderson et al, 1972).…”
Section: Bacterial Strains Bacteriophage and Plasmidsmentioning
confidence: 99%
“…been in the laboratory for over 40 years (Alexander and Leidy, 1951); DB117 was obtained from G. Barcak (University of Maryland) (Setlow et at., 1968), H. inftuenzae strain 12 is the non-typable strain from which the genes encoding the HMW1 and HMW2 proteins were cloned (Barenkamp and Leininger, 1992); HMW1 and HMW2 are the prototyptc members of a family of non-typable Haemcphilus antigenically related high-molecular-weight adhesive proteins (St. Geme efa/., 1993).…”
Section: Discussionmentioning
confidence: 99%